A preliminary study on the measuring training intensity in swimming - Lei, S.; Chang, X. (The Hong Kong Journal of Sports Medicine and Sports, 2000)
It is very important for coaches to evaluate the change of swimmer training level exactly. The measurement of blood lactate is a usual method to monitor the training intensity and fitness levels. To evaluate the change of training level exactly, pace and blood lactate are two factors that have to be noted simultaneously. There aren't any expression including pace and blood lactate that evaluate quantitatively the change of training level till now. The purpose of this article is to analyze feasibility of the expression V/lnBL to evaluate the training level exactly in aerobic-anaerobic mixed training(AAMT) and lactate training(LT). Thirty-two swimmers took part in this study. It was researched that effect of training levels before two National Championships on race results in 16 months. The data on training was collected from exercise sessions during the SOth-2Oth day before competitions. AAMT was finished in 2 kind of intermittent training means: 8 x 50m with a 30s rest, 4 x 100m with a 40s rest, blood lactate value had to be in 5-9 mM/L. LT was finished in 2 kind of intermittent training means: 8 x 50m with a I minute rest, or 4 x l00m with a 2 minutes rest, blood lactate value was above ID mM/L. The performance and blood lactate with freestyle in all of AAMT and LT during 16 months was studied also. The results show that the correlation coefficient was higher between race result and V/lnBL than between race result and performance. It was indicated that V/lnBL was more sensitive to express the change of individual training level in AAMT and LI than performance. It was supported by data that the higher intensity was, the lower V/lnBL value was in same style swimming training. In same relative intensity training, the performance was significant difference between sexes, there was no sex difference in V/lnBL value to expressed training level. A complete explanation of these results on V/lnBL must await further investigation.